RADULA, OPERCULUM AND CONTRAOPERCULUM OF THE CRETACEOUS AMMONITE ACONECERAS (MOLLUSCA, CEPHALOPODA) - Doguzhayeva L.A.; Mutvey H. (My University, 1990)
A ridged radula with its characteristic multiapical (5 to 11 denticles) rachidial and first and second lateral teeth has been found for the first time in ammonites. The operculum, contraoperculum and radula, which together form the remains of the buccal complex in Aconeceras, were studied in successive sections polished with diamond pastes having grain sizes of 3.0, 1.0 and 0.5 μm, and then etched with 0.5 to 2.0 percent solutions of hydrochloric acid for 5 to 10 sec. The general shape of the radula, the number of its tooth rows in different ontogenetic stages and the structure of the individual teeth could be observed in three dimensions under the optical microscope, because the living chambers were filled with transparent calcite. With the scanning electron microscope we studied the sections through the radular teeth, particularly their microstructure of these teeth, and also counted the number of denticles on the rachidial and lateral teeth.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая